EPIC 216747137: a new HW Vir eclipsing binary with a massive sdOB primary and a low-mass M-dwarf companion. Issue 2 (27th October 2020) - Silvotti, R; Schaffenroth, V; Heber, U; Østensen, R H; Telting, J H; Vos, J; Kilkenny, D; Mancini, L; Ciceri, S; Irrgang, A; Drechsel, H
ABSTRACT: EPIC 216747137 is a new HW Virginis system discovered by the Kepler spacecraft during its K 2 'second life'. Like the other HW Vir systems, EPIC 216747137 is a post-common-envelope eclipsing binary consisting of a hot subluminous star and a cool low-mass companion. The short orbital period of 3.87 h produces a strong reflection effect from the secondary (∼9 per cent in the R band). Together with AA Dor and V1828 Aql, EPIC 216747137 belongs to a small subgroup of HW Vir systems with a hot evolved sdOB primary. We find the following atmospheric parameters for the hot component: T eff  = 40400 ± 1000 K, log  g  = 5.56 ± 0.06, and log( N (He)/ N (H)) = −2.59 ± 0.05. The sdOB rotational velocity v  sin   i  = 51 ± 10 km s −1 implies that the stellar rotation is slower than the orbital revolution and the system is not synchronized. When we combine photometric and spectroscopic results with the Gaia parallax, the best solution for the system corresponds to a primary with a mass of about 0.62 M⊙ close to, and likely beyond, the central helium exhaustion, while the cool M-dwarf companion has a mass of about 0.11 M⊙ .